2018
DOI: 10.4172/2161-0509.1000238
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prevalence of Malnutrition among Children Age 6-59 Months at Woreda 06, Gulele Subcity, Addis Ababa, Ethiopia, 2017

Abstract: Background: Child illness and death in Ethiopia are primarily due to five common childhood illnesses, namely pneumonia (ARI), diarrhea, malaria, measles, and malnutrition and often combination of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This study indicated the magnitude of underweight was 10.2% (95% CI (7.3% − 13.9%)), it is lower than the study reported from Pakistan, the study reported from Tanzania (14%)(26), Nigeria (33.3%) (25) and study conducted in India (36%) (23). Likewise, very far from study reported from Tigray (45.3%) (27), Addis Ababa (54.1 (9) and study reported from Somalia region (east Ethiopia) (19.5%) (9). The variation is due to socioeconomic difference and due to methodological discrepancy.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This study indicated the magnitude of underweight was 10.2% (95% CI (7.3% − 13.9%)), it is lower than the study reported from Pakistan, the study reported from Tanzania (14%)(26), Nigeria (33.3%) (25) and study conducted in India (36%) (23). Likewise, very far from study reported from Tigray (45.3%) (27), Addis Ababa (54.1 (9) and study reported from Somalia region (east Ethiopia) (19.5%) (9). The variation is due to socioeconomic difference and due to methodological discrepancy.…”
Section: Discussionmentioning
confidence: 54%
“…In Addis Ababa, the prevalence of malnutrition and classi es it according its degree which is 55.1%, 57.7% and 49.26% measured with weight for age, weight for height and mid upper arm circumference respectively (9).…”
Section: Introductionmentioning
confidence: 99%